The Cost of Public Funding with Direct and Indirect Taxation - a Revisit - Bjart J. Holtsmark; Katinka Kristine Holtsmark (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The paper shows that the marginal cost of public funds (MCF) does not depend on whether public revenue is collected by taxation of consumer goods or income from factors supplied by households on the market. Atkinson and Stern (1974) concluded in their seminal paper that “[...] whether the Conventional Rule provides an under- or over-estimate depends on the choice of taxed good [....].” This conclusion has created confusion in the literature on the MCF and has been the basis for recent literature arguing that the standard measure of the MCF has weaknesses and should be replaced by alternative measures (Jacobs, 2018; Håkonsen, 1998). We show that the conclusion of Atkinson and Stern (1974) on this issue is not valid and is based on an error in their analysis.
Keywords: H20; H40; H50; 330; marginal cost of public funds; taxation; Samuelson rule